Devolution and Governance - Cole, Alistair. author. aut Link
X, 162 p.
Keywords: This book examines the development of Welsh devolution in the context of great economic and political uncertainty. Drawing on research carried out over more than a decade, it explores whether Welsh devolution has developed the capacity to resist internal and external pressures and to continue to pursue a distinctive political and policy agenda.